1994
DOI: 10.1002/rcm.1290080305
|View full text |Cite
|
Sign up to set email alerts
|

Halocarbenes as diagnostic tools for mass spectral localization of double bonds

Abstract: Different halocyclopropanes prepared by cycloaddition of halocarbenes to olefins by phase-transfer reactions have been analyzed by gas chromatography/mass spectrometry (GUMS). Starting from CCI,-adducts, the investigations have been extended to bromine-and fluorine-containing cyclopropanes. As reaction partners, a group of olefins, containing different alkyl substituents, have been selected. Thereby, special attention has been paid to smooth reaction conditions, high reaction yield and simple handling. The sui… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0

Year Published

1996
1996
2016
2016

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 15 publications
0
4
0
Order By: Relevance
“…Scherch et al investigated the use of halocarbenes in cyclopropane reactions to fix the location of the double bonds. 378 In their study employing CBr 2 , CCl 2 , CF 2 , CClF, CHCl, CHF, and CBrF, they found that bromofluorocarbene was the most useful. This conclusion was based on the high reactivity of bromofluorocarbene coupled with the ease in identifying the adduct fragments due to its characteristic isotopic patterns.…”
Section: Bromofluorocarbenementioning
confidence: 99%
See 2 more Smart Citations
“…Scherch et al investigated the use of halocarbenes in cyclopropane reactions to fix the location of the double bonds. 378 In their study employing CBr 2 , CCl 2 , CF 2 , CClF, CHCl, CHF, and CBrF, they found that bromofluorocarbene was the most useful. This conclusion was based on the high reactivity of bromofluorocarbene coupled with the ease in identifying the adduct fragments due to its characteristic isotopic patterns.…”
Section: Bromofluorocarbenementioning
confidence: 99%
“…Bis(trifluoromethyl)carbene ( 397) is a highly electrophilic species due to the two electron-withdrawing trifluoromethyl groups. Two useful precursors for its photochemical or thermal generation are bis(trifluoromethyl)diazomethane (375) and bis(trifluoromethyl)diazirine (378).…”
Section: B Bis(trifluoromethyl)carbenementioning
confidence: 99%
See 1 more Smart Citation
“…Chemical derivatization procedures that involve the conversion of structures containing double bonds to other chemical structures that retain their structural information upon analysis by mass spectrometry or other analytical techniques have been developed in the past. However, these procedures are often time-consuming and cannot be easily implemented for the routine analysis of olefins. A faster and more sensitive approach is to selectively ionize the olefinic structures in the chemical ionization (CI) source of a mass spectrometer by ion−molecule reactions.…”
mentioning
confidence: 99%